Dating the origins of the maize-adapted strain of maize streak virus, MSV-A - Harkins, Gordon W; Martin, Darren P; Duffy, Siobain; Monjane, Aderito L; Shepherd, Dionne N; Windram, Oliver P; Owor, Betty E; Donaldson, Lara; van Antwerpen, Tania; Sayed, Rizwan A; Flett, Bradley; Ramusi, Moses; et al. (Journal of general virology, 2009)
Maize streak virus (MSV), which causes maize streak disease (MSD), is one of the most serious biotic threats to African food security. Here, we use whole MSV genomes sampled over 30 years to estimate the dates of key evolutionary events in the 500 year association of MSV and maize. The substitution rates implied by our analyses agree closely with those estimated previously in controlled MSV evolution experiments, and we use them to infer the date when the maize-adapted strain, MSV-A, was generated by recombination between two grass-adapted MSV strains. Our results indicate that this recombination event occurred in the mid-1800 s, approximately 20 years before the first credible reports of MSD in South Africa and centuries after the introduction of maize to the continent in the early 1500 s. This suggests a causal link between MSV recombination and the emergence of MSV-A as a serious pathogen of maize.